The Mediating Effect of Depression on the Relation Between Interpersonal Needs and Suicidal Ideation Among Chinese Transgender Women - Chang, Ruijie; Zeng, Chengbo; Qiao, Shan; Wang, Huwen; Xu, Chen; Yu, Xiaoyue; Ma, Tiecheng; Wang, Ying; Li, Xiaoming; Cai, Yong (Frontiers in Public Health, 2022)
Background Transgender women are at high risk of depression and suicidal ideation. Interpersonal Theory of Suicide proposes that suicidal ideation could be a consequence of high interpersonal needs (thwarted belongingness and perceived burdensomeness). The current study aimed to test this theory and investigated whether depression could mediate the relationship between interpersonal needs and suicidal ideation among transgender women in Shenyang, China. Methods 198 transgender women were recruited by snowball sampling. A cross-sectional study was conducted through structured questionnaire. Suicidal ideation, depression and interpersonal needs were assessed. Path analysis was used to carry out the research goals and the mediating effect of depression was tested. Results There were nearly 37% of the participants reporting suicidal ideation. Suicidal ideation was positively correlated with thwarted belongingness (t = -5.53, p < 0.01) and perceived burdensomeness (t = -5.02, p < 0.01). The direct effect from thwarted belongingness to suicidal ideation via depression was statistically significant (std.β = 0.232, p < 0.01). Depression mediated the indirect path from perceived burdensomeness to suicidal ideation (std.β = 0.222, p < 0.01) although the direct path between them was not significant (std.β = 0.046, p = 0.693). Conclusions Depression fully mediated the relationship between perceived burdensomeness and suicidal ideation, and partially mediate the relationship between thwarted belongingness and suicidal ideation. Interventions targeting thwarted belongingness, perceived burdensomeness, and depression are needed.